Knowledge on pre-hospital emergency management of tooth avulsion among Croatian kindergarten teachers - Užarević, Zvonimir (Array, 2020)
The aim of this study was to evaluate knowledge on pre-hospital emergency management of tooth avulsion among Croatian kindergarten teachers. A cross-sectional study was conducted among 33 educators in kindergarten (average 43.9±9.7 years). The questionnaire contained 10 close-ended questions with two or eleven possible answers. Statistical significance was determined using chi-square test. Majority of participants had no experience with tooth injury among children in kindergarten. Questions about the familiarity with the terms of a knocked-out tooth and tooth replantation and whether the knocked-out tooth should be replanted were confirmatively answered by 90.9%, 57.6% and 63.6% of participants, respectively. Only 9.1% of participants provided the correct answer that replantation should be done within 30 minutes. 78.8% of participants would choose correct medium for cleaning if avulsed tooth got dirty. Tooth would be transported in appropriate medium by 48.5% of participants. Correct answers on both the transport medium and the cleaning of knocked-out tooth were provided by 45.5% participants. 57.6% participants would seek help for replantation by visiting the nearest dentist. None of the participants had ever received any kind of information on management of a knocked-out tooth. The kindergarten teachers have a lack of knowledge for immediate response to tooth avulsion. Every kindergarten teacher should be well informed what should be done if some type of dental injury happens. The official communication between dental professionals and kindergarten teachers should be improved at local and regional level.